Building Engagement, Building Futures: An Empirical Analysis To Maximize Youth Engagement in the UK Job Market - Gupta, Payal; Malla, Biraj; Allgaier, Hildenguard (2012)
It is evident that young people have been largely affected by the recession as companies have decreased their offers, complicating Youth employability and, consequently, reducing their chances to get experience and job connections. Moreover, current recruitment practices emphasise aspects which do not help and most young people today can no longer count on the prospect of a job for life‘. However, the market is changing and the picture looks quite promising. Companies financial statements have demonstrated this recovering specially in the UK and sectors such as Accounting, Investment Banking, and the Public Sector expect to recruit more graduates in 2012/2013. This report aims to understand how young people between 18-24 years old engage themselves in the UK job market and how Working for Youth‘, an initiative dedicated by Standard Chartered Bank and Experian can maximise this engagement through their online channels.